2011
DOI: 10.1088/0067-0049/193/2/30
|View full text |Cite
|
Sign up to set email alerts
|

UV-TO-FIR ANALYSIS OF SPITZER /IRAC SOURCES IN THE EXTENDED GROTH STRIP. II. PHOTOMETRIC REDSHIFTS, STELLAR MASSES, AND STAR FORMATION RATES

Abstract: Based on the ultraviolet to far-infrared photometry already compiled and presented in a companion paper (Paper I), we present a detailed spectral energy distribution (SED) analysis of nearly 80,000 IRAC 3.6 + 4.5 μm selected galaxies in the Extended Groth Strip. We estimate photometric redshifts, stellar masses, and star formation rates (SFRs) separately for each galaxy in this large sample. The catalog includes 76,936 sources with [3.6] 23.75 (85% completeness level of the IRAC survey) over 0.48 deg 2 . The t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 135 publications
5
112
0
Order By: Relevance
“…We obtained consistent photometry by applying a single aperture across all optical and near-IR bands. We also extracted IRAC photometry, applying the procedure described in Pérez-González et al (2008) and Barro et al (2011a) to deblend the IRAC photometry when a single IRAC source is associated with multiple optical/near-IR counterparts.…”
Section: Cdfs Cdfn and Egsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained consistent photometry by applying a single aperture across all optical and near-IR bands. We also extracted IRAC photometry, applying the procedure described in Pérez-González et al (2008) and Barro et al (2011a) to deblend the IRAC photometry when a single IRAC source is associated with multiple optical/near-IR counterparts.…”
Section: Cdfs Cdfn and Egsmentioning
confidence: 99%
“…We have also identified stars with fainter magnitudes that are detected at X-ray wavelengths and removed them from our samples. In the fields with Rainbow coverage (CDFS, CDFN, EGS) stars were identified by a range of colour and morphology criteria, as described in Barro et al (2011a). In the COSMOS and Bootes fields we applied a single colour criterion based on the region of colour-colour space occupied by stars in Ilbert et al (2009)…”
Section: Identification and Masking Of Starsmentioning
confidence: 99%
“…Sorba & Sawicki (2010) and Barro et al (2011) showed that the [3.6]−[4.5] color is a useful photometric redshift indicator, especially for separating galaxies at z 1.3 from those at z 1.5. Figure 30 shows a color-magnitude diagram of the SEDS sources.…”
Section: Irac Color Distributionmentioning
confidence: 99%
“…Bell et al 2005;Papovich et al 2007;Barro et al 2011) of and 3000 Å, L UV , is estimated as 1.5νf ν, 2800 , where f ν, 2800 is the rest-frame luminosity at 2800 Å. For further details of this process, see Taylor et al (in preparation).…”
Section: Long-duration Uv Continuum + Tir Luminosity Sfrmentioning
confidence: 99%